Π‐Conjugation Enables Ultra‐High Rate Capabilities and Cycling Stabilities in Phenothiazine Copolymers as Cathode‐Active Battery Materials. (1st September 2019) - Acker, Pascal; Rzesny, Luisa; Marchiori, Cleber F. N.; Araujo, C. Moyses; Esser, Birgit
Abstract: In recent years, organic battery cathode materials have emerged as an attractive alternative to metal oxide–based cathodes. Organic redox polymers that can be reversibly oxidized are particularly promising. A drawback, however, often is their limited cycling stability and rate performance in a high voltage range of more than 3.4 V versus Li/Li + . Herein, a conjugated copolymer design with phenothiazine as a redox‐active group and a bithiophene co‐monomer is presented, enabling ultra‐high rate capability and cycling stability. After 30 000 cycles at a 100C rate, >97% of the initial capacity is retained. The composite electrodes feature defined discharge potentials at 3.6 V versus Li/Li + due to the presence of separated phenothiazine redox centers. The semiconducting nature of the polymer allows for fast charge transport in the composite electrode at a high mass loading of 60 wt%. A comparison with three structurally related polymers demonstrates that changing the size, amount, or nature of the side groups leads to a reduced cell performance. This conjugated copolymer design can be used in the development of advanced redox polymers for batteries. Abstract : Boosting the rate capability, conjugated phenothiazine copolymers show excellent cycling stability at a 100C rate in a battery cathode at a stable discharge potential of 3.6 V versus lithium as the anode. This is achieved by combining defined phenothiazine redox centers with a conjugated polymer backbone.